PEMIKIRAN ISLAM KH. ABDURRAHMAN WAHID (GUS DUR) TENTANG PENDIDIKAN: ANALISIS TERHADAP KONSEPNYA - Sugiyantoro, Sugiyantoro; Haryono, Pauzan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study explores Islamic thought on education in the form of its concept from the perspective of KH. Abdurrahman Wahid. In the context of concern about the impact of globalization called future shocks, researchers see a lack of clear concepts in the world of Indonesian education to face this current of globalization. This study focuses on the thoughts of KH. Abdurrahman Wahid on the concept of Islamic education that reflects neomodernism, with efforts to maintain traditional values ??while absorbing western modernization. This study uses a library research method, also known as library research whose information is collected through library research, This study is included in the category of